Nano-based drug delivery systems for the treatment of non-infectious uveitis - Xingdi Wu; Mengyuan Hu; Yilu Cai; Fan Jia; Yang Ye; Naiji Yu; Min Chen; Kaijun Wang (Advances in Ophthalmology Practice and Research)
Background: Uveitis is one of the most prevalent causes of global visual impairment. The current approaches to treating non-infectious uveitis (NIU) involve the utilization of corticosteroids, immunosuppressant and biologics agents. Nevertheless, the intricate ocular anatomy barriers and adverse side effects of the drugs pose significant obstacles to effective treatment outcomes. Main text: To improve drug bioavailability and therapeutic outcomes for NIU while minimize side effects, researchers are committed to developing novel nano-based drug delivery systems (DDS), which have the capacity to achieve targeted delivery, increase bioavailability, achieve sustained release, reduce side effects and improve therapeutic effects. Thus, DDS based on nanotechnology, including liposome, dendrimer, hydrogels, nanoparticles, nanomicelles, nanosuspensions and nanoemulsions have emerged as promising alternatives to conventional ocular delivery methods for the management of NIU. Conclusions: In this review, we summarize the current therapeutic challenges faced by NIU and describe various nano-based intraocular DDS involved in the treatment of NIU. It is concluded that nano-based DDS is an appealing approach to addressing the unmet needs for the treatment of NIU.